Cognitive Enhancing and Neuroprotective Effect of the Embryo of the Nelumbo nucifera Seed. (24th December 2014) - Kim, Eun Sil; Weon, Jin Bae; Yun, Bo-Ra; Lee, Jiwoo; Eom, Min Rye; Oh, Kyoung-Hee; Ma, Choong Je
Abstract : The aim of the present study was to evaluate the effect of ENS on cognitive impairment induced by scopolamine and its potential neuroprotective effect against glutamate-induced cytotoxicity in HT22 cell and to investigate the underlying mechanisms. ENS (3, 10, 30, and 100 mg/kg), scopolamine (1 mg/kg), and donepezil (1 mg/kg) were administered to mice during a test period. Scopolamine impaired memory and learning in a water maze test and a passive avoidance test. The neuroprotective effect of ENS (10 and 100  μ g/mL) was investigated on glutamate-induced cell death in HT22 cells by MTT assay. We investigated acetylcholinesterase inhibition in hippocampus and antioxidant activity, ROS levels, and Ca 2+ influx in HT22 cells to elucidate the potential mechanisms of ENS. We found that ENS significantly ameliorated scopolamine-induced memory impairment and inhibited AChE activity in hippocampus. In vitro, ENS showed potent neuroprotective effects against glutamate-induced neurotoxicity in the HT22 cell. In addition, ENS induced a decrease in ROS production and intercellular Ca 2+ accumulation and showed DPPH radical and H2 O2 scavenging activity. In conclusion, ENS showed both a memory improving effect and a neuroprotective effect. Our results indicate that ENS may be of use in the treatment and prevention of neurodegenerative disorders.